Novel Design Concept of an Optoelectronic Integrated RF Communication Module. (2016) - Dao, Quang Huy; Skubacz-Feucht, Alexandra; Lüers, Bernard; von Witzendorff, Philipp; von der Ahe, Christoph; Overmeyer, Ludger; Geck, Bernd
Abstract: This contribution presents a novel design concept of a 24 GHz radio frequency communication module. The integration of optical and electrical components is a particular challenge since the module is miniaturized in order to be integrated into any metallic workpieces. The design concept and the scope of functions of the communication unit acting as a wireless sensor node are discussed. The development of a highly integrated radio frequency circuit and the realization of through glass vias are some main aspects. The central control unit is an ultra-low power microcontroller capable of a flexible connection of sensors. By using an energy harvesting concept consisting of a solar cell with an efficiency of 40% and a supercapacitor the availability of energy is unlimited. Different lighting conditions are investigated in order to evaluate the available power of the solar cell. Furthermore, the power supply is investigated concerning voltage-current characteristics and the resulting operating time of the whole unit for a low ambient light scenario.